Perception of medical students regarding E-learning during lockdown in COVID–19 pandemic: A cross-sectional study in a medical college, North Kerala - Punathukandi, Sruthikrishna; Nair, Meera Sivadasan; Kaithery, Nivya Noohiyil (Indian Journal of Community Health, 2022)
Background: The digital learning in this pandemic era of COVID-19 evolved out in a perplexed environment as a viable alternative to offline or traditional classes. The e-learning carries its own merits as well as demerits, but however, this happened to be the only possible solution in this dreaded situation. With respect to medicos, as they are prone to be exposed to environments connected with Covid infected patients, additional care including online classes turned to be the better option. Aim and Objective: To determine the perception of medical students regarding e-learning during lockdown in COVID-19 pandemic. Settings and Design: A cross-sectional study was conducted among medical students of all the batches in a private medical College, Kozhikode. Methods and Material: Primary data were collected using structured Google questionnaire. Stratified sampling method has been adopted and the sample size was 400. Statistical analysis used: Data analysed using SPSS 18 software. Results: Majority of the participants used Zoom as modality of learning and half of the total participants got adapted to the system over time. During e-learning sessions, most of the medicos expressed their concerns regarding lack of clinical exposure, in addition to their losses in social communication skills. Factors such as the legitimate requirements of clinical phase students, issues of poor internet connectivity and health problems were inclined to demand traditional learning, which were statistically significant. Conclusion: Even though they were subjected to both online and offline methods of education, majority of respondents preferred traditional learning.